Prevention and correction of disorders in the development of the “core” in reader’s competence of children with disabilities (based on education of children with deep impairments of vision and hearing) - Goncharova, Elena (Social Welfare: Interdisciplinary Approach, 2013)
The article is devoted to the problem of forming an ability to transform the meaning which the author has introduced in a text implicitly into own cognitive, emotional and creative experience of children with disabilities. The stages and methodical conditions for forming this ability in children with impairments of vision and hearing are described.
Keywords: disorders of reading of children; reader’s competence; transition from situational to contextual speaking; children with special needs; children with disabilities; deaf-blind children